Safety practice towards zero accident at construction site / Mohd Tariq Yusop - Yusop, Mohd Tariq (Faculty of Architecture,Planning and Surveying, 2015)
Good safety practice ensures the construction will be running smoothly without any unwanted accidents. For safety practice in construction site, the safety practices are crucial since the construction site is exposed to danger. In the construction site, accidents occur usually can causes the fatalities, permanent disabilities, and non-permanent disability to the victim. This accident can be avoided from continuously occur. That means an accidents during construction at the construction site due to the mistake can be controlled and reducing from time to time.The worker needs to follow the rules and regulation in construction to reduce the hazard. This research is conducted to study the safety practice towards zero accident at construction site. To achieve the objective in this research, researcher is able to produce three objectives which are to study the safety on site, to determine the safety practice used in construction site and to give recommendation on safety practices at construction site. Questionnaires were distributed to the worker at construction site. The results from the data analysis shows that safety practices used in the construction industry is need to be improved in order to reduce the accidents.